A lightweight porous carbonized plate and a preparation method thereof
By mixing carbon mineralized materials and nanosilicon dioxide with water, pressing the molded plate, and using carbon dioxide gas during the carbonization process, ultrasonic alkali washing is carried out after carbonization, lightweight porous carbonized plates are prepared, which solves the problems of complex preparation process, high cost and poor adsorption performance of existing plates, and achieves efficient adsorption and environmentally friendly production process.
Patent Information
- Application Number
- CN202310281164.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-03-17
AI Technical Summary
The preparation process of existing new plates is complex, costly, and poor adsorption performance, making it difficult to meet the demand for lightweight and porous materials in green and low-carbon buildings.
Lightweight porous carbonized plates are prepared by mixing carbon mineralized materials and nanosilicon dioxide with water, pressing the molded plates, and using carbon dioxide gas during the carbonization process, and ultrasonic alkali washing is performed after carbonization.
The prepared carbonized plate has excellent adsorption performance, which can effectively enhance the adsorption effect on moisture and gas, and at the same time achieve the purpose of saving costs, recycling waste and reducing greenhouse effects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0004138060480000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbonized plates, and in particular relates to a lightweight porous carbonized plate and a preparation method thereof. Background Art
[0002] Green and low-carbon buildings should not only reduce carbon emissions during the construction process, but also significantly reduce daily energy consumption and emissions. Therefore, in the consumer market for construction and decoration materials, the cost pressure of raw materials for construction and decoration materials consumer products is evident.
[0003] New board materials are an important research direction in building decoration. The use of new materials to make the boards lighter can reduce the pressure on the walls. However, the preparation process of existing new boards is complicated, the cost is high, and the adsorption performance is poor. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a lightweight porous carbonized plate and a preparation method thereof. The carbonized plate prepared by the method is lightweight and has excellent adsorption performance.
[0005] The present invention provides a method for preparing a lightweight porous carbonized plate, comprising the following steps:
[0006] mixing the carbon mineralized material, nano-silicon dioxide and water to obtain a mixed material;
[0007] Pressing the mixed material to obtain a formed plate;
[0008] The formed plate is carbonized to obtain a lightweight porous carbonized plate.
[0009] The mass ratio of the carbon mineralization material to the nano-silicon dioxide is 9:1 to 6:4.
[0010] In the present invention, the water accounts for 10-40% of the total mass of the carbon mineralization material and nano-silicon dioxide.
[0011] In the present invention, the carbonization pressure is 0.1-0.6 MPa, and the carbonization time is 8-60 h;
[0012] The volume concentration of carbon dioxide in the carbonization gas used in the carbonization is ≥3%.
[0013] In the present invention, the carbon mineralization material is selected from one or more of calcium oxide, calcium hydroxide, magnesium oxide, magnesium hydroxide, calcium silicate, magnesium silicate, steel slag, furnace slag, magnesium slag, carbide slag, thiourea slag, γ-dicalcium silicate, β-dicalcium silicate, monocalcium silicate and tricalcium disilicate.
[0014] In the present invention, the formed sheet is alkali washed after carbonization, and then washed with water until neutral, to obtain a lightweight porous carbonized sheet;
[0015] The alkaline washing method is ultrasonic alkaline washing; the alkaline washing adopts 4-8 mol / L sodium hydroxide solution;
[0016] The temperature of the alkali washing is 50-90° C., and the time of the alkali washing is greater than or equal to 30 minutes.
[0017] The present invention provides a lightweight porous carbonized plate, which is prepared by the preparation method described in the above technical solution.
[0018] The present invention provides a method for preparing a lightweight porous carbonized plate, comprising the following steps: mixing a carbon mineralized material, nano-silicon dioxide and water to obtain a mixed material; pressing the mixed material to obtain a formed plate; carbonizing the formed plate to obtain a lightweight porous carbonized plate. The carbonized plate prepared by the method has dense and uniform pores, which can effectively enhance the adsorption of moisture and gas by the plate; the preparation process is a "carbon neutral" process, which achieves the purpose of cost saving, waste recycling, and reducing the greenhouse effect. At the same time, the preparation process is highly operable and suitable for industrialization, achieving the purpose of recycling carbon dioxide and lightweight adsorption. The experimental results show that the carbonized plate is lightweight and porous; the iodine adsorption value is 400-529 mg / g; and the modulus of rupture is 3.6-8.2 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The figure is a schematic diagram of the process of preparing a lightweight porous carbonized plate according to a specific embodiment of the present invention. DETAILED DESCRIPTION
[0020] The present invention provides a method for preparing a lightweight porous carbonized plate, comprising the following steps:
[0021] mixing the carbon mineralized material, nano-silicon dioxide and water to obtain a mixed material;
[0022] Pressing the mixed material to obtain a formed plate;
[0023] The formed plate is carbonized to obtain a lightweight porous carbonized plate.
[0024] The present invention mixes a carbon mineralization material with nano silicon dioxide and water to obtain a mixed material. In the present invention, the carbon mineralization material is preferably rich in one or more materials selected from calcium oxide, calcium hydroxide, magnesium oxide, magnesium hydroxide, calcium silicate and magnesium silicate; the components in the carbon mineralization material preferably also include one or more selected from steel slag, furnace slag, magnesium slag, carbide slag, thiourea slag, γ-dicalcium silicate, β-dicalcium silicate, monocalcium silicate and tricalcium disilicate. In a specific embodiment of the present invention, the carbon mineralization material is γ-dicalcium silicate or steel slag.
[0025] In the present invention, the particle size of the nano-silicon dioxide is 1 to 100 nm. The mass ratio of the carbon mineralization material to the nano-silicon dioxide is preferably 9:1 to 6:4. In a specific embodiment, the mass ratio of the carbon mineralization material to the nano-silicon dioxide is 9:1; or 8:2; or 7:3; or 6:4.
[0026] The amount of water added is 10-40wt% of the total amount of the material. The addition of water is helpful for compression molding and has little effect on the carbonization effect.
[0027] After obtaining the mixed material, the present invention presses the mixed material to obtain a formed plate. The present invention preferably places the mixed material in a sample pressing mold to press it into a plate.
[0028] The present invention carbonizes the formed sheet to obtain a lightweight porous carbonized sheet. In the present invention, the carbonization pressure is 0-0.6MPa, and the carbonization time is 8-60h; in a specific embodiment, the carbonization pressure is 0.1MPa, and the carbonization time is 24h; the volume concentration of carbon dioxide in the carbonization gas used in the carbonization is ≥3%, which helps carbon dioxide enter the sheet to participate in the reaction, and the carbonization is more complete; the carbonization process is a carbon neutralization process, and the carbonization gas can be industrial waste gas, which realizes waste utilization and effectively reduces production costs.
[0029] The present invention preferably performs alkali washing after carbonization, and then washes with water until neutral to obtain a lightweight porous carbonized plate; the alkali washing method is ultrasonic alkali washing; the alkali washing adopts 4-8 mol / L sodium hydroxide solution; the alkali washing temperature is 50-90°C, and the alkali washing time is greater than or equal to 30 minutes; the ultrasonic frequency of the ultrasonic alkali washing is 60% and above, which is helpful to clean the nano-silicon dioxide and remove it more cleanly. In a specific embodiment, the alkali washing adopts 6 mol / L sodium hydroxide solution; the alkali washing time is 30 minutes, the alkali washing temperature is 50°C; the ultrasonic frequency is 60%.
[0030] Figure 1 This is a schematic diagram of the process for preparing a lightweight porous carbonized plate material used in a specific embodiment of the present invention.
[0031] The present invention provides a lightweight porous carbonized plate, which is prepared by the preparation method described in the above technical solution. The lightweight and porous characteristics of the carbonized plate can enhance the plate's adsorption of moisture and gas.
[0032] In order to further illustrate the present invention, a lightweight porous carbonized plate material and a preparation method thereof provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0033] Example 1
[0034] A lightweight porous carbonized sheet preparation process, variable conditions (γ-dicalcium silicate and nano-silicon dioxide are uniformly mixed in a ratio of 9:1)
[0035] 1. Evenly mix γ-dicalcium silicate and nano silicon dioxide in a ratio of 9:1, add 30% of the total amount of water, and continue to mix evenly;
[0036] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0037] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0038] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution to ultrasonically clean it for 0.5 h, with the ultrasonic temperature of 50°C and the ultrasonic frequency of 60%. Then wash it with distilled water until the solution is neutral, and a lightweight porous carbonized plate can be obtained.
[0039] Example 2
[0040] A lightweight porous carbonized sheet preparation process, variable conditions (γ-dicalcium silicate and nano-silicon dioxide are uniformly mixed in a ratio of 8:2)
[0041] 1. Evenly mix γ-dicalcium silicate and nano silicon dioxide in a ratio of 8:2, add 30% of the total amount of water, and continue to mix evenly;
[0042] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0043] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0044] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0045] Example 3
[0046] A lightweight porous carbonized sheet preparation process, variable conditions (γ-dicalcium silicate and nano-silicon dioxide are uniformly mixed in a ratio of 7:3)
[0047] 1. Evenly mix γ-dicalcium silicate and nano silicon dioxide in a ratio of 7:3, add 30% of the total amount of water, and continue to mix evenly;
[0048] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0049] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0050] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0051] Example 4
[0052] A lightweight porous carbonized sheet preparation process, variable conditions (γ-dicalcium silicate and nano-silicon dioxide are uniformly mixed in a ratio of 6:4)
[0053] 1. Evenly mix γ-dicalcium silicate and nano silicon dioxide in a ratio of 6:4, add 30% of the total amount of water, and continue to mix evenly;
[0054] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0055] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0056] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0057] Example 5
[0058] A lightweight porous carbonized plate preparation process, variable conditions (steel slag and nano-silicon dioxide are uniformly mixed in a ratio of 8:2)
[0059] 2. Evenly mix the steel slag and nano-silicon dioxide in a ratio of 8:2, add 30% of the total amount of water, and continue to mix evenly;
[0060] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0061] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0062] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0063] Example 6
[0064] A lightweight porous carbonized plate preparation process, variable conditions (steel slag and nano-silicon dioxide are uniformly mixed in a ratio of 7:3)
[0065] 3. Evenly mix the steel slag and nano-silicon dioxide in a ratio of 7:3, add 30% of the total amount of water, and continue to mix evenly;
[0066] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0067] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0068] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0069] Example 7
[0070] A lightweight porous carbonized sheet preparation process, variable conditions (γ-dicalcium silicate and nano-silicon dioxide are uniformly mixed in a ratio of 8:2)
[0071] 1. Evenly mix γ-dicalcium silicate and nano silicon dioxide in a ratio of 8:2, add 10% of the total amount of water, and continue to mix evenly;
[0072] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0073] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0074] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0075] Example 8
[0076] A lightweight porous carbonized sheet preparation process, variable conditions (γ-dicalcium silicate and nano-silicon dioxide are uniformly mixed in a ratio of 8:2)
[0077] 1. Evenly mix γ-dicalcium silicate and nano silicon dioxide in a ratio of 8:2, add 20% of the total amount of water, and continue to mix evenly;
[0078] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0079] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0080] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0081] Example 9
[0082] A lightweight porous carbonized sheet preparation process, variable conditions (γ-dicalcium silicate and nano-silicon dioxide are uniformly mixed in a ratio of 8:2)
[0083] 1. Evenly mix γ-dicalcium silicate and nano silicon dioxide in a ratio of 8:2, add 40% of the total amount of water, and continue to mix evenly;
[0084] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0085] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0086] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0087] Example 10
[0088] A lightweight porous carbonized sheet preparation process, variable conditions (γ-dicalcium silicate and nano-silicon dioxide are uniformly mixed in a ratio of 8:2)
[0089] 1. Evenly mix γ-dicalcium silicate and nano silicon dioxide in a ratio of 8:2, add 50% of the total amount of water, and continue to mix evenly;
[0090] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0091] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0092] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0093] Embodiment 11
[0094] A lightweight porous carbonized plate preparation process, variable conditions (steel slag and nano-silicon dioxide are uniformly mixed in a ratio of 8:2)
[0095] 1. Mix steel slag and nano-silicon dioxide in a ratio of 8:2, add 20% of the total amount of water, and continue to mix evenly;
[0096] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0097] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0098] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0099] Example 12
[0100] A lightweight porous carbonized plate preparation process, variable conditions (steel slag and nano-silicon dioxide are uniformly mixed in a ratio of 7:3)
[0101] 1. Mix steel slag and nano-silicon dioxide in a ratio of 8:2, add 30% of water to the total amount of the material, and continue to mix evenly;
[0102] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0103] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0104] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, the ultrasonic temperature is 50°C, the ultrasonic frequency is 60%, and then wash it with distilled water until the solution is neutral to obtain a lightweight porous carbonized plate.
[0105] Comparative Example 1
[0106] A carbonized sheet preparation process, variable conditions (no nano-silicon dioxide added)
[0107] 1. Add 30% of the total amount of water to the steel slag and mix well;
[0108] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0109] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0110] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, with the ultrasonic temperature of 50°C and the ultrasonic frequency of 60%, and then wash it with distilled water until the solution is neutral, that is, the carbonized plate.
[0111] Comparative Example 2
[0112] A carbonized sheet preparation process, variable conditions (no nano-silicon dioxide added)
[0113] 1. Add 30% of the total amount of water to γ-dicalcium silicate and mix well;
[0114] 2. Place the mixed material into a sample pressing mold and press it into a plate;
[0115] 3. Place the plate in a carbonization tank and carbonize it with carbon dioxide at a pressure of 0.1 MPa for 24 hours;
[0116] 4. Take out the carbonized plate and use 6 mol / L sodium hydroxide solution for ultrasonic cleaning for 0.5 h, with the ultrasonic temperature of 50°C and the ultrasonic frequency of 60%, and then wash it with distilled water until the solution is neutral, that is, the carbonized plate.
[0117] Based on the above examples 1 to 6 and comparative examples 1 to 2, the following analysis is made:
[0118] Table 1 Test results of Examples 1 to 6 and Comparative Examples 1 to 2
[0119]
[0120] It can be seen from Table 1 that (1) when the addition ratio of γ-dicalcium silicate to nano-silicon dioxide is 8:2, the iodine adsorption value is the best and the overall product effect is the best; (2) as the mass of nano-silicon dioxide increases, the overall quality of the board product decreases, and the iodine adsorption value first increases and then decreases. The reason is that the number of macropores increases and the iodine adsorption value decreases; therefore, the preferred mixing ratio of γ-dicalcium silicate to nano-silicon dioxide is 8:2.
[0121] Table 2 Performance test results of the plate of the embodiment
[0122]
[0123] It can be seen from Table 2 that the amount of added water directly affects the degree of carbonization and the strength of the board. The modulus of rupture first increases and then decreases with the increase of the amount of added water, and the modulus of rupture is the highest when the water amount is 30%. When the amount of added water reaches 50%, obvious fractures have begun to appear on the surface of the board. Therefore, the amount of added water can be preferably 30%.
[0124] It can be seen from the above embodiments that the present invention provides a method for preparing a lightweight porous carbonized plate, comprising the following steps: mixing a carbon mineralized material with nano-silicon dioxide and water to obtain a mixed material; pressing the mixed material to obtain a molded plate; carbonizing the molded plate to obtain a lightweight porous carbonized plate. The carbonized plate prepared by this method has dense and uniform pores, which can effectively enhance the adsorption of moisture and gas by the plate; the preparation process is a "carbon neutral" process, which achieves the purpose of cost saving, waste recycling, and reducing the greenhouse effect. At the same time, the preparation process is highly operable and suitable for industrialization, achieving the purpose of recycling carbon dioxide and lightweight adsorption. The experimental results show that the carbonized plate is lightweight and porous; the iodine adsorption value is 400-529 mg / g; and the modulus of rupture is 3.6-8.2 MPa.
[0125] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a lightweight porous carbonized plate, comprising the following steps: The carbon mineralization material, nano-silicon dioxide and water are mixed to obtain a mixed material; the mass ratio of the carbon mineralization material to the nano-silicon dioxide is 9:1-6:4; the water accounts for 10-40% of the total mass of the carbon mineralization material and the nano-silicon dioxide; the carbonization pressure is 0.1-0.6 MPa, and the carbonization time is 8-60 hours; the volume concentration of carbon dioxide in the carbonization gas used in the carbonization is ≥3%; the carbon mineralization material is selected from steel slag and / or γ-dicalcium silicate; Pressing the mixed material to obtain a formed plate; The formed sheet is carbonized, alkali washed after carbonization, and then washed with water until neutral to obtain a lightweight porous carbonized sheet; The alkaline washing method is ultrasonic alkaline washing; the alkaline washing adopts 4-8 mol / L sodium hydroxide solution; The temperature of the alkali washing is 50-90° C., and the time of the alkali washing is greater than or equal to 30 minutes.
2. A lightweight porous carbonized plate, characterized in that: Prepared by the preparation method described in claim 1.
Citation Information
Patent Citations
Calcium carbonate-based sand powder reinforced carbonized hardened body and preparation method thereof
CN113121192A
Low-alkalinity high-strength pervious concrete as well as preparation method and application thereof
CN114477942A